Telling about something verbally: A semantic syntax study - Hammad, Anas (Al-Adab Journal, 2024)
This research deals with one of the rhetorical methods of the Arabs, which is telling about something with its verbal synonym, whether the synonym is complete or incomplete, and it is a method that appears to be ambiguous. If it is not understood with a mind devoid of the margin of the text or the semantics around it, rather it needs to bring in the necessary contexts to understand the speaker’s intent. It also aims to convey the semantic image closest to the speaker’s intent, or the possible interpretative or estimative connotations, and the researcher seeks here to establish general rules for understanding and interpreting this method, drawing from the words of linguists and interpreters to serve the texts of the Arab Islamic and literary heritage. This research aims to introduce the reader to this style and present the traditional evidence for it from the Qur’an, Sunnah, poetry and prose. I did not find any previous researchers who dealt with this method or referred to it, but the ancients commented on its texts and interpreted them and interpreted the ambiguous ones in a way that suits the verbal context without putting it in a title or under a chapter. For that reason, I tried to put the appropriate title for it, so its title was (Telling about something verbally, A semantic syntax study), and the term information is broader than the term grammatical predicate, Because the information does not necessarily adhere to the predicate in parsing, and it is one of the mainstays in the grammarians’ terminology, but rather it goes beyond it to what they term by virtues, so it informs them and strengthens them in terms of significance and effect. Because the information does not necessarily adhere to the predicate in parsing, and it is one of the mainstays in the grammarians’ terminology, but rather it goes beyond it to what they term by virtues, so it informs them and strengthens them in terms of significance and effect. This method can only be understood through grammatical and semantic contexts based on taking them from the imams of the ancestors, grammarians, and commentators. It has become clear from examining and extrapolating the speech of the Arabs that the meanings to which this method emerges are limited - mostly - to aspects, namely: glorification, contempt, exaggeration, suspense, and threat. Other meanings may emerge depending on the verbal context. The research also aims to seek to convey the semantic image that is closest to the speaker’s intention, or the interpretive or evaluative implications it may have. The researcher here also seeks to establish general or approximate rules. To understand and interpret this method, drawing conclusions from the words of scholars in a way that serves the texts of the Arab Islamic and literary heritage.